Analisis Faktor-Faktor yang Berhubungan dengan Lama Rawat Inap Pasien Pneumonia Komunitas di RSUD Kota Kendari (Analysis of Factors Associated with Length of Stay in Community-Acquired Pneumonia Patients at RSUD Kota Kendari) - Kolewora, Yusuf Musafir; Ali, Nurharpen; Arimaswati, Arimaswati (Jurnal Ilmiah Global Education, 2025)
Community-Acquired Pneumonia (CAP) is a leading cause of hospitalization with high morbidity and mortality rates. The length of stay (LOS) of patients with CAP is an important indicator of healthcare effectiveness, as it affects costs, risk of complications, and quality of care. Factors such as age, sex, comorbidities, qSOFA, and PSI have been reported to play a role in determining LOS in patients with CAP, including at RSUD Kota Kendari. This study used an observational analytic method with a retrospective cross-sectional approach. The sample consisted of 89 hospitalized CAP patients from January to December 2024 who met the inclusion and exclusion criteria, selected using purposive sampling. Data were analyzed using the chi-square test and Spearman’s correlation, with p<0.05 considered statistically significant. The results showed that most CAP patients experienced a prolonged hospital stay. Statistical analysis revealed significant associations between age (p=0.000; r=0.488), comorbidities (p=0.003), and PSI score (p=0.000; r=0.407) with the length of stay. Sex (p=1.000) and qSOFA score (p=0.103) were not significantly associated. Older age and higher PSI scores were significantly associated with a longer length of hospital stay in CAP patients at RSUD Kota Kendari, with a positive correlation. Comorbidities were also significantly associated with the length of stay, while sex and qSOFA score showed no significant association with a longer length of hospital stay in CAP patients at RSUD Kota Kendari.